Comprehensive assessment of physiological responses in women during the ESA dry immersion VIVALDI microgravity simulation - Adrien Robin; Angelique Van Ombergen; Claire Laurens; Audrey Bergouignan; Laurence Vico; Marie-Thérèse Linossier; Anne Pavy-Le Traon; Marc Kermorgant; Angèle Chopard; Guillaume Py; David Andrew Green; Michael Tipton; et al. (Nature Communications, 2023)
Abstract Astronauts in microgravity experience multi-system deconditioning, impacting their inflight efficiency and inducing dysfunctions upon return to Earth gravity. To fill the sex gap of knowledge in the health impact of spaceflights, we simulate microgravity with a 5-day dry immersion in 18 healthy women (ClinicalTrials.gov Identifier: NCT05043974). Here we show that dry immersion rapidly induces a sedentarily-like metabolism shift mimicking the beginning of a metabolic syndrome with a drop in glucose tolerance, an increase in the atherogenic index of plasma, and an impaired lipid profile. Bone remodeling markers suggest a decreased bone formation coupled with an increased bone resorption. Fluid shifts and muscular unloading participate to a marked cardiovascular and sensorimotor deconditioning with decreased orthostatic tolerance, aerobic capacity, and postural balance. Collected datasets provide a comprehensive multi-systemic assessment of dry immersion effects in women and pave the way for future sex-based evaluations of countermeasures.